Periodization of Innovative Enterprises Process Approach (Economic journal of Lesya Ukrainka Volyn National University, 2015)
Considered periods innovative development of enterprises by process approach. Posted five stages of innovative businesses. Highlight the following stages of innovation development as the manufacturing and technical innovation crisis of innovation and technological innovation and management. Accordingly, the proposed periodyzuvaty innovative enterprise development as an innovative enterprise development first, second, third, fourth and fifth waves.Established that there are different approaches to the formation of periodization system innovation. Theories of Innovation Development process approach for enterprises grouped in the following areas: 1) theory of organization and production management (development of innovative businesses first and second waves); 2) the cyclical theory of economic development (the development of innovative companies second and third waves); 3) innovative theories of technological change (development of innovative enterprises fourth wave); 4) the current concept of innovation (innovative development of enterprises fifth wave).In these areas the factors of economic development of technological capacity, innovation, knowledge for humane capital. Process approach provides for innovative development in specific business processes that form the whole system of innovative enterprise development.Indicated that factors in the economic development of the theory of organization and production management is the technical potential, cyclical theory of economic development - capital, labor, technical potential. In the innovative theory of technological change the main drivers of economic development is innovation, entrepreneurs, knowledge and human capital. Modern concepts of innovative use of factors, in addition to innovation, and more humane capital and, in particular, more attention to the human factor than other types
Keywords: innovations, innovative development company, the new economy, enterprise, waves of innovation development